Sound the alarm: A meta‐analysis on the effect of aquatic noise on fish behavior and physiology. (24th March 2018) - Cox, Kieran; Brennan, Lawrence P.; Gerwing, Travis G.; Dudas, Sarah E.; Juanes, Francis
Abstract: The aquatic environment is increasingly bombarded by a wide variety of noise pollutants whose range and intensity are increasing with each passing decade. Yet, little is known about how aquatic noise affects marine communities. To determine the implications that changes to the soundscape may have on fishes, a meta‐analysis was conducted focusing on the ramifications of noise on fish behavior and physiology. Our meta‐analysis identified 42 studies that produced 2, 354 data points, which in turn indicated that anthropogenic noise negatively affects fish behavior and physiology. The most predominate responses occurred within foraging ability, predation risk, and reproductive success. Additionally, anthropogenic noise was shown to increase the hearing thresholds and cortisol levels of numerous species while tones, biological, and environmental noise were most likely to affect complex movements and swimming abilities. These findings suggest that the majority of fish species are sensitive to changes in the aquatic soundscape, and depending on the noise source, species responses may have extreme and negative fitness consequences. As such, this global synthesis should serve as a warning of the potentially dire consequences facing marine ecosystems if alterations to aquatic soundscapes continue on their current trajectory. Abstract : A variety of noise pollutants bombards the aquatic environment. However, little is known about how noise affects marine communities. To address this concern, a meta‐analysis on the ramifications of sound on fish behavior and physiology was conducted. The most predominate responses to anthropogenic noise occurred within foraging ability, predation risk, hearing thresholds, cortisol levels, and reproductive success. Tones, biological, and environmental noise affected complex movements and swimming abilities. These findings suggest that the majority of fish species are sensitive to changes in the aquatic soundscape, and depending on the noise source, species responses may have negative fitness consequences.